AUREA MEDIOCRITAS: HEROES AND FAKE HEROES/ANTIHEROES IN ROMANIAN HODONYMY - FELECAN, Oliviu (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Aurea mediocritas: Heroes and Fake Heroes/Antiheroes in Romanian Hodonymy. Specialised literature has shown that, regardless of geographical space and historical era, authorities have sought to honour heroes and grant them “immortality” by giving their names to various roadways: streets, boulevards, squares. From a socio- and psycholinguistic viewpoint, there is the issue of associating positive or negative values with the given figures depending on the political regime. Those who are seen as heroes at one point in time can be considered war criminals at a different moment in history. Similarly, the heroes of a certain nation can be the sworn enemies of a neighbouring people. Therefore, a theory of values needs to be advanced, a balance in judgement that should be above the circumstantial interests of those in power. This study analyses Romanian hodonymy from the aforementioned perspective. Since the officialization of street nomenclature, Romanian hodonyms have been subjected to several processes of street-name changes, determined by the unification of the country, the world wars, the various stages of the institution of the communist regime, and the establishment of democracy after 1989. Names of streets and squares are eloquent markers of all the onomastic changes that have occurred in Romanian space over different historical periods. REZUMAT. Aurea mediocritas: eroi/falși eroi/antieroi în hodonimia românească. Literatura de specialitate a arătat că, indiferent de spațiul geografic și de epoca istorică, autoritățile au căutat să cinstească eroii și să le acorde „nemurirea,” dându-le numele diferitelor drumuri: străzi, bulevarde, piețe. Din punct de vedere socio- și psiholingvistic, se pune problema asocierii valorilor pozitive sau negative cu percepția oamenilor în funcție de regimul politic. Cei care sunt văzuți ca eroi la un moment dat pot fi considerați criminali de război într-un moment diferit al istoriei. În mod similar, eroii unei anumite națiuni pot fi dușmanii declarați ai unui popor vecin. Prin urmare, trebuie avansată o teorie a valorilor, un echilibru în judecată care să fie deasupra intereselor de moment ale celor de la putere. Acest studiu analizează hodonimia românească din perspectiva menționată mai sus. De la oficializarea nomenclaturii stradale, hodonimele românești au fost supuse mai multor procese de schimbare/transformare, determinate de unirea țării, războaiele mondiale, diferitele etape ale instaurării regimului comunist și redobândirea democrației după 1989. Denumirile străzilor și piețelor sunt repere elocvente ale tuturor schimbărilor onomastice care s-au produs în spațiul românesc în diferite perioade istorice. Cuvinte-cheie: hodonimie, schimbări de peisaj urban, eroi/antieroi/falși eroi, nume de străzi. Article history: Received 26 May 2023; Revised 2 July 2023; Accepted 12 September 2023; Available online 30 September 2023; Available print 30 September 2023.